Cloning, characterization and differential expression of an hsp70 gene from the pathogenic dimorphic fungus, Penicillium marneffei - Aksarakorn Kummasook (2018)
A gene encoding heat shock protein 70 (Hsp70) of Penicillium marneffei was isolated and characterized. The structure of P. marneffei hsp70 gene was similar to hsp70 genes of other organisms, with a unique sequence of 3-nt microexon flanked by two introns. Comparison of the deduced amino acid sequence revealed that the Hsp70 was grouped in the fungal cytosolic Hsp70s. Northern blot analysis demonstrated the upregulation of hsp70 expression during the mycelium to yeast phase transition. Upregulation was also observed during yeast or mycelial cells encountering heat shock condition at 39°C. Experimental analysis showed that the expression of hsp70 is temperature dependent. Contradictory, a severe heat shock condition at 42°C resulted in lowering the hsp70 transcript. Reverse transcription-polymerase chain reaction (RT-PCR) showed the accumulation of a large population of mature mRNA and small population of intron II-unspliced hsp70 mRNA in most cell types (conidia, mycelia and yeast). These results suggested that the Hsp70 may play an important role in environmental stress response and adaptation. © 2007 Informa UK Ltd.